Fabrication, phase formation and microstructure of Ni4Nb2O9 ceramics fabricated by using the two-stage sintering technique - Khamman O. (2017)
© 2016, The Korean Physical Society. The potential utilization of two-stage sintering for the production of very dense and pure nickel diniobate (Ni 4 Nb 2 O 9 ) ceramics with low firing temperature was demonstrated. The effects of the designed sintering conditions on the phase formation, densification and microstructure of the ceramics were characterized by using X-ray diffraction (XRD), Archimedes method and scanning electron microscopy (SEM), respectively. The minor phase of columbite NiNb 2 O 6 tended to form together with the desired Ni 4 Nb 2 O 9 phase, depending on the sintering conditions. Optimization of the sintering conditions may lead to a single-phase Ni 4 Nb 2 O 9 ceramics with an orthorhombic structure. The ceramics doubly sintered at 950/1250 ◦C for 4 h exhibited a maximum density of ~92%. Microstructures with denser angular grain-packing were generally found in the sintered Ni 4 Nb 2 O 9 ceramics. However, the grains were irregular in shape when the samples were sintered at 1050/1250 ◦C. Two-stage sintering was also found to enhance the ferroelectric behavior of the Ni 4 Nb 2 O 9 ceramic.